Benefits of Understanding Systemic Racism in Forming Clinician-Patient Relationships to Reduce Black Infant Mortality - Michelle A. Gotto; Laura Morello; Marsha Michie (Ohio Journal of Public Health, 2020)
Background: The United States lags far behind other developed nations in our overall infant mortality rate. Public health researcher Arline Geronimus has described a "weathering" effect of chronic racial stress among Black women that contributes to high rates of preterm birth, the leading cause of infant death. Trusting relationships between clinicians and patients may play a role in reducing infant mortality for Black mothers. Based on a social-ecological model of health care communication around infant mortality, we focus here on doctor-patient communication and correlations between clinicians' understandings of systemic racism and their communication with Black pregnant patients. Methods: This paper reports the findings from interviews with 5 maternal health clinicians (prior to recruitment being temporarily paused due to COVID-19) practicing at Cuyahoga County hospitals that serve large populations of Black women. Qualitative coding methods based in grounded theory were used to draw out themes from interview transcripts. Results: Doctor-patient communication was an emergent theme in these interviews. Results suggest an association between clinicians' understanding of the impact of systemic racism and their ability to communicate successfully and form positive bonds with pregnant mothers who are at higher risk of infant mortality. Conclusion: Acknowledging systemic racism as the cause of poor social determinants of health, which in turn contribute to higher rates of infant mortality, may provide clinicians a pathway to more positive communication and higher levels of trust with their patients, which in turn may play a role in reducing infant mortality in the Black community. Further research should investigate these associations.
Keywords: Infant mortality; Systemic racism; Communication; Clinician-patient relationship; Implicit bias